Determinants of Actuarial Cost Method Changes for Pension Accounting and Funding. - Ghicas, Dimitrios C. (The Accounting Review, 1990)
Abstract Identifies and evaluates potential determinants of the switch from cost-allocation actuarial method to a benefit-allocation actuarial cost method. Effects of the switch; Causes of the decrease in pension expense and funding; Reasons for the switch in actuarial cost methods.